DAMPAK PANDEMI COVID-19 TERHADAP VOLATILITAS HARGA ECERAN BEBERAPA KOMODITAS PANGAN DI JABODETABEK - Ria Kusumaningrum; Rahmah Farahdita Soeyatno (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2021)
Since the Covid-19 pandemic food commodity prices in Greater Jakarta (Jabodetabek) have tended to be unstable. In this regard, the effectiveness of food price stabilization policies is determined by the availability of complete information and a better understanding of the volatility of the commodity prices concerned. This research is intended to analyze and compare the volatility of food commodity prices, namely rice, chicken, beef and eggs as staple food and food sources of protein needed during the pandemic. The data is divided into two periods, namely the period before and after the Covid-19 pandemic. The results showed the method of forecasting the daily retail price of food commodities in Indonesia requires a different approach. For beef commodities the more appropriate approach is the ARCH/GARCH model. For the commodity of rice, chicken meat and eggs forecasting methods with the ARIMA model. Defined daily retail prices for beef commodities in the period after the Covid-19 pandemic are more volatile than in the pre-pandemic period. It is also evident that during religious holidays the retail price of beef becomes more volatile. In fact, the increase in volatility tends to be sustainable.